Exosomal CD44 Transmits Lymph Node Metastatic Capacity Between Gastric Cancer Cells via YAP-CPT1A-Mediated FAO Reprogramming - Wang, Mei; Yu, Wanjun; Cao, Xiaoli; Gu, Hongbing; Huang, Jiaying; Wu, Chen; Wang, Lin; Sha, Xin; Shen, Bo; Wang, Ting; Yao, Yongliang; Zhu, Wei; et al. (Frontiers in Oncology, 2022)
Background Lymph node metastasis (LNM) commonly occurs in gastric cancer (GC) and is tightly associated with poor prognosis. Exosome-mediated lymphangiogenesis has been considered an important driver of LNM. Whether exosomes directly transmit the LNM phenotype between GC cells and its mechanisms remain elusive. Methods A highly lymphatic metastatic GC cell line (HGC-27-L) was established by serial passage of parental HGC-27 cells in BALB/c nude mice. The capacities of migration, invasion and LNM; fatty acid oxidation (FAO) levels; and the role of exosome-transferred LNM phenotype were compared among HGC-27-L, HGC-27 and primary GC cell line AGS. Exosomes derived from GC cells and sera were separately isolated using ultracentrifugation and ExoQuick exosome precipitation solution, and were characterized by transmission electron microscopy, Nanosight and western blotting. Transwell assay and LNM models were conducted to evaluate the capacities of migration, invasion and LNM of GC cells in vitro and in vivo. β-oxidation rate and CPT1 activity were measured to assess FAO. CPT1A inhibitor etomoxir was used to determine the role of FAO. Label-free LC-MS/MS proteome analysis screened the differential protein profiling between HGC-27-exosomes and AGS-exosomes. Small interference RNAs and YAP inhibitor verteporfin were used to elucidate the role and mechanism of exosomal CD44. TCGA data analysis, immunochemistry staining and ELISA were performed to analyze the expression correlation and clinical significance of CD44/YAP/CPT1A. Results FAO was increased in lymphatic metastatic GC cells and indispensable for sustaining LNM capacity. Lymphatic metastatic GC cell-exosomes conferred LNM capacity on primary GC cells in an FAO-dependent way. Mechanistically, CD44 was identified to be enriched in HGC-27-exosomes and was a critical cargo protein regulating exosome-mediated transmission, possibly by modulating the RhoA/YAP/Prox1/CPT1A signaling axis. Abnormal expression of CD44/YAP/CPT1A in GC tissues was correlated with each other and associated with LNM status, stages, invasion and poor survival. Serum exosomal CD44 concentration was positively correlated with tumor burden in lymph nodes. Conclusions We uncovered a novel mechanism: exosomal CD44 transmits LNM capacity between GC cells via YAP-CPT1A-mediated FAO reprogramming from the perspective of exosomes-transferred LNM phenotype. This provides potential therapeutic targets and a non-invasive biomarker for GC patients with LNM.